Association of Bariatric Surgery Using Laparoscopic Banding, Roux-en-Y Gastric Bypass, or Laparoscopic Sleeve Gastrectomy vs Usual Care Obesity Management With All-Cause Mortality - Reges, Orna; Greenland, Philip; Dicker, Dror; Leibowitz, Morton; Hoshen, Moshe; Gofer, Ilan; Rasmussen-Torvik, Laura J; Balicer, Ran D (JAMA : the journal of the American Medical Association, 2018)
Bariatric surgery is an effective and safe approach for weight loss and short-term improvement in metabolic disorders such as diabetes. However, studies have been limited in most settings by lack of a nonsurgical group, losses to follow-up, missing data, and small sample sizes in clinical trials and observational studies. To assess the association of 3 common types of bariatric surgery compared with nonsurgical treatment with mortality and other clinical outcomes among obese patients. Retrospective cohort study in a large Israeli integrated health fund covering 54% of Israeli citizens with less than 1% turnover of members annually. Obese adult patients who underwent bariatric surgery between January 1, 2005, and December 31, 2014, were selected and compared with obese nonsurgical patients matched on age, sex, body mass index (BMI), and diabetes, with a final follow-up date of December 31, 2015. A total of 33 540 patients were included in this study. Bariatric surgery (laparoscopic banding, Roux-en-Y gastric bypass, or laparoscopic sleeve gastrectomy) or usual care obesity management only (provided by a primary care physician and which may include dietary counseling and behavior modification). The primary outcome, all-cause mortality, matched and adjusted for BMI prior to surgery, age, sex, socioeconomic status, diabetes, hyperlipidemia, hypertension, cardiovascular disease, and smoking. The study population included 8385 patients who underwent bariatric surgery (median age, 46 [IQR, 37-54] years; 5490 [65.5%] women; baseline median BMI, 40.6 [IQR, 38.5-43.7]; laparoscopic banding [n = 3635], gastric bypass [n = 1388], laparoscopic sleeve gastrectomy [n = 3362], and 25 155 nonsurgical matched patients (median age, 46 [IQR, 37-54] years; 16 470 [65.5%] women; baseline median BMI, 40.5 [IQR, 37.0-43.5]). The availability of follow-up data was 100% for all-cause mortality. There were 105 deaths (1.3%) among surgical patients during a median follow-up of 4.3 (IQR, 2.8-6.6) years (including 61 [1.7%] who underwent laparoscopic banding, 18 [1.3%] gastric bypass, and 26 [0.8%] sleeve gastrectomy), and 583 deaths (2.3%) among nonsurgical patients during a median follow-up of 4.0 (IQR, 2.6-6.2) years. The absolute difference was 2.51 (95% CI, 1.86-3.15) fewer deaths/1000 person-years in the surgical vs nonsurgical group. Adjusted hazard ratios (HRs) for mortality among nonsurgical vs surgical patients were 2.02 (95% CI, 1.63-2.52) for the entire study population; by surgical type, HRs were 2.01 (95% CI, 1.50-2.69) for laparoscopic banding, 2.65 (95% CI, 1.55-4.52) for gastric bypass, and 1.60 (95% CI, 1.02-2.51) for laparoscopic sleeve gastrectomy. Among obese patients in a large integrated health fund in Israel, bariatric surgery using laparoscopic banding, gastric bypass, or laparoscopic sleeve gastrectomy, compared with usual care nonsurgical obesity management, was associated with lower all-cause mortality over a median follow-up of approximately 4.5 years. The evidence of this association adds to the limited literature describing beneficial outcomes of these 3 types of bariatric surgery compared with usual care obesity management alone.